Comparison Between the Constant Dummy Load and Step Load Shut‐Down Strategy for PEMFCs1. Issue 3 (30th March 2018) - Lin, R.; Xia, S.; Zhang, Q.; Dutruel, B.
Abstract: Carbon corrosion of catalyst layer (CL) caused by start‐up/shut‐down (SU/SD) conditions in proton exchange membrane fuel cells (PEMFCs) decreases the durability of the membrane electrode assembly (MEA). It is reported that the dummy load shut‐down strategy helps alleviating the carbon corrosion. In this paper, constant load strategy and step load strategy are applied during 900 SU/SD cycles each, to investigate the effects of different dummy load forms on the durability of PEMFC. Reversal current is observed during the last phase of 5 A constant loading process, while there is no reversal current during the step load strategy. The results obtained through polarization curves, cyclic voltammetry (CV) and scanning electron microscope (SEM) technologies, prove the step load strategy more efficient to alleviate the performance decay. Therefore, the step load strategy can improve the durability of PEMFC.